Analysis of the Legal State of Ground Communities - Kwartnik-Pruc, Anita; Mączyńska, Aneta (Geomatics and Environmental Engineering, 2020)
There are over 5,000 land communities in Poland that own real estate with an area of over 100,000 hectares. In 2009, the Supreme Audit Office (SAO, in Polish the Najwyższa Izba Kontroli) carried out an audit of the factual and legal status of State Treasury property and municipal property. The inspection also included properties belonging to land communities and showed numerous irregularities in their functioning throughout Poland. The result of the audit was large changes to the Law regulating the operation of land communities, i.e. the Law of June 29, 1963 on the Development of Land Communities. The amended act was intended to facilitate the regulation of the legal status of many properties in Poland. This article presents an analysis of the legal status of real estate of land communities made on the basis of the audit carried out in 2009 by the Supreme Audit Office. The article presents the procedure of regulating the legal status of real estate according to the provisions of the amended Law on the management of land communities. Furthermore, it contains the analysis of administrative proceedings concerning land community in selected counties located in the Masovian Voivodeship (i.e. the district of Ostrołęka and the district of Przysucha) to check whether the amended law helped to regulate the legal status of community lands and land communities.